2020
DOI: 10.5603/ep.a2020.0056
|View full text |Cite
|
Sign up to set email alerts
|

Bone densitometry by radiofrequency echographic multi-spectrometry (REMS) in acromegaly patients

Abstract: Introduction: Radiofrequency echographic multi-spectrometry (REMS) is a recently introduced non-ionising technology employed in the evaluation of osteoporosis. The aim of our study was to compare bone mineral density (BMD) in acromegaly patients and healthy controls by performing novel REMS densitometry. The second objective was to analyse the correlation between results of REMS and classical dual-energy X-ray absorptiometry (DXA) in acromegaly patients. 2 Material and methods: We enrolled 33 patients with acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the TCA group as well as in the TCA+ CA group, TBS was decreased in comparison to controls, while BMD was similar among these groups. These results confirmed that TBS and BMD reflect different features of bone and explain the incident of fractures in acromegaly, despite the normal BMD values ( 28 , 29 ). This can be explained by the fact that lower TBS value reflects impaired bone microstructure, which is associated with higher fracture risk.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the TCA group as well as in the TCA+ CA group, TBS was decreased in comparison to controls, while BMD was similar among these groups. These results confirmed that TBS and BMD reflect different features of bone and explain the incident of fractures in acromegaly, despite the normal BMD values ( 28 , 29 ). This can be explained by the fact that lower TBS value reflects impaired bone microstructure, which is associated with higher fracture risk.…”
Section: Discussionsupporting
confidence: 78%
“…The disruption of trabecular bone is caused by the decreased trabecular number and increased trabecular separation. For these reasons, fractures could be present in acromegaly patients with normal or slightly decreased BMD ( 11 , 28 , 29 ). Hong et al.…”
Section: Discussionmentioning
confidence: 99%
“…Trabecular bones are more prone to GH overproduction than cortical bones, which leads to impairment of its structural integrity ( 22 ). Therefore, in patients with acromegaly, fractures occur even with normal or slightly decreased BMD ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated REMS measurements have captured the reduction in BMD, caused by the commencement of AI and the increase in BMD which follows treatment of these patients with denosumab [ 17 ]. REMS effectiveness has also been verified in further single-centre studies of patients with anorexia nervosa or with rare diseases such as osteogenesis imperfecta or acromegaly [ 40 42 ].…”
Section: Chronic Disorders Affecting the Skeletonmentioning
confidence: 90%